1974
DOI: 10.1128/jb.118.1.213-224.1974
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Messenger Ribonucleic Acids and Proteins Synthesized by the Bacteriocinogenic Factor Clo DF13 in Purified Minicells of Escherichia coli

Abstract: It has previously been shown that the cloacinogenic factor Clo DF13 (Clo DF13) segregates into minicells of strain Escherichia coli P678-54 that harbors Clo DF13 and that this Clo DF13 factor is the only deoxyribonucleic acid (DNA) present in these otherwise chromosomeless minicells. The study reported here shows that minicells prepared from P678-54(Clo DF13) are able to incorporate radioactive precursors into ribonucleic acid (RNA) and protein. The RNA synthesized in these purified minicells is Clo DF13 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Radioactive labeling of these minicells with [3H]uridine revealed that minicells harboring CloDF13 cop-3 incorporated label into trichloroacetic acid-insoluble material (2.75 x 103 cpm per ml of culture per 30 min), whereas no significant incorporation was observed in plasmidless minicells. These results are in good agreement with those reported previously (14). The incorporation of [3H]uridine observed in minicells containing CloDF13 cop-3 could be completely blocked by the addition of rifampin (0.1 mg/ml), whereas chloramphenicol (0.15 mg/ ml) had no detectable effect.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Radioactive labeling of these minicells with [3H]uridine revealed that minicells harboring CloDF13 cop-3 incorporated label into trichloroacetic acid-insoluble material (2.75 x 103 cpm per ml of culture per 30 min), whereas no significant incorporation was observed in plasmidless minicells. These results are in good agreement with those reported previously (14). The incorporation of [3H]uridine observed in minicells containing CloDF13 cop-3 could be completely blocked by the addition of rifampin (0.1 mg/ml), whereas chloramphenicol (0.15 mg/ ml) had no detectable effect.…”
Section: Resultssupporting
confidence: 93%
“…Kool et al. (14) reported the identification of at least four plasmid-specific mRNA's isolated from minicells harboring plasmid CloDF13 cop-3.…”
mentioning
confidence: 99%
“…These data also offer strong support for a role for these cell proteins in R factor DNA function. Recent findings in our laboratory as well as others (13) demonstrate a decrease in macromolecular biosynthetic activity as minicells age. These results suggest that certain cell products essential for R factor function are being lost and cannot be regenerated in the absence of' cell DNA.…”
Section: Discussionsupporting
confidence: 58%
“…(iii) Chromosomeless minicells from strain P678-54 harboring the mutant Clo DF13 plasmid synthesize about six times more deoxyribonucleic acid, ribonucleic acid, and protein as compared to wild-type Clo DF13-harboring minicells. (iv) Analysis of this mutant Clo DF13-specific ribonucleic acid and protein on polyacrylamide gels revealed mainly the same ribonucleic acid and polypeptide species as synthesized by the wild-type Clo DF13 minicells, but in larger amounts (Kool et al, 1974). (v) Segregation experiments, using a strain with temperature-sensitive polymerase I, show that mutant Clo DF13-harboring cells contain an average of 70 Clo DF13 copies per cell, whereas wild-type Clo DF13-harboring cells contain only about 10 Clo DF13 copies per cell.…”
mentioning
confidence: 83%